An Analysis of Satires in Green Book Movie by Peter Farrely - Malvino Erlanditya Dilapanga; Kartin Lihawa; Usman Pakaya (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Satire is a form of literary device that mock the foolishness of individual, group or even a society Its goal is to highlight flaws or foolishness in the hope that it will encourage improvement. This study aims to analyzes the use of satire in Peter Farrelly’s film Green Book, focusing on the types of satire employed and their communicative functions. Utilizing M.H. Abrams’ classification of satire (Horatian, Juvenalian, Menippean), the research adopts a qualitative descriptive approach to examine dialogues from the movie script. The analysis centers on the interactions between the main characters, to identify how satirical elements address themes of racism, social inequality, and cultural disparity. The findings reveal nineteen instances of satire: eight Horatian, characterized by humor and irony to critique societal norms gently; ten Juvenalian, employing direct and harsh criticism to confront racial injustices; and two Menippean, highlighting situational irony and mental attitudes. Tony Lip predominantly uses Juvenalian satire to challenge systemic racism, while Dr. Shirley employs Horatian satire to navigate cultural tensions subtly. Menippean satire, though less frequent, underscores contradictions in societal perceptions. This research contributes to linguistic studies by expanding the understanding of satire’s role in cinematic discourse, particularly in addressing complex social issues. It highlights the efficacy of satire as a tool for social critique, offering insights into how different satirical styles reflect characters’ backgrounds and societal dynamics. The study provides a foundation for future interdisciplinary research on satire in media, emphasizing its relevance in contemporary cultural and political contexts.